2020
DOI: 10.1371/journal.pone.0238049
|View full text |Cite
|
Sign up to set email alerts
|

Asia-wide phylogeography of wild boar (Sus scrofa) based on mitochondrial DNA and Y-chromosome: Revising the migration routes of wild boar in Asia

Abstract: Genetics of pigs has been well studied in Europe and Asia, but most of previous studies of molecular phylogeny of Sus scrofa have been based on sequences of both wild and domestic forms. In this study we analysed genetic traits of Sus scrofa from 13 regions in Asia (including previously undisclosed Eastern Caucasus and Trans-Baikal regions) using purely wild boar samples. Mitochondrial control region and Y-chromosome genes (AMELY & USP9Y) were employed to resolve phylogeographic relationships. We discussed spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…The species has also been introduced by humans to all other continents (except Antarctica) and many islands 1 . Wild boar evolved in South-Eastern Asia, and then colonized northern, central and western parts of Eurasia in several migration waves 2 , 3 . Omnivorous and ecologically flexible, the species occurs in many different temperate and tropical habitats from forests, marshes and grasslands to semi-deserts 1 , 4 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The species has also been introduced by humans to all other continents (except Antarctica) and many islands 1 . Wild boar evolved in South-Eastern Asia, and then colonized northern, central and western parts of Eurasia in several migration waves 2 , 3 . Omnivorous and ecologically flexible, the species occurs in many different temperate and tropical habitats from forests, marshes and grasslands to semi-deserts 1 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…There have been several phylogenetic studies performed on wild boar in Eurasia 2 , 3 , 19 22 , which revealed two or three main mtDNA lineages of wild boar: the Asian (or East Asian and Near Eastern) and the European one divided further into clades. However, the phylogenetic positions of these lineages and clades varied among studies due to different length, number, and geographic distribution of analysed sequences (comp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of molecular genetic methods makes it possible to characterize animal populations and determine the degree of their genetic differentiation. Various types of DNA markers are used to characterize the wild boar populations from Russia: mitochondrial DNA [ 10 , 11 , 12 ], Y-chromosome [ 12 , 13 ], STR [ 14 , 15 , 16 , 17 ], SNP [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In East Asia, many previous studies have focused on the origin and the recolonization history of domestic pigs [ 16 , 17 ]. The phylogeography of the Asia-wide wild boar revealed that the wild boar migrated from South-East Asia to South Asia, followed by migration to East and West Asia [ 18 ]. Geographical barriers, such as the complex topography of mountains and islands in east and central China, long-term gene flow and population history, play an important role in driving the formation of complex spatial genetic structure of wild boar in East Asia [ 19 ].…”
Section: Introductionmentioning
confidence: 99%